Immature granulocytes predict severe acute pancreatitis independently of systemic inflammatory response syndrome - Michał Lipiński; Grażyna Rydzewska (Gastroenterology Review)
Introduction : Early prediction of severity of acute pancreatitis (AP) by a simple parameter that positively correlates with the activation stage of the immune system would be very helpful because it could influence the management and improve the outcome. Tumor necrosis factor α (TNF-α) and interleukin-1 (IL-1) play a critical role in the pathogenesis systemic inflammatory response syndrome (SIRS) and severity of AP. One of the effects of IL-1 and TNF-α is an increase in the number of immature granulocytes (IGs) in the peripheral blood. Aim : To assess whether the IGs% in plasma could be an independent marker of AP severity. Material and methods : A cohort of 77 patients with AP were prospectively enrolled in the study. The IGs were measured from whole blood samples obtained from the first day of hospitalization using an automated analyser. Results : We observed 44 (57%) patients with mild AP, 21 (27%) patients with moderate severe AP (SAP) and 12 (16%) patients with SAP. The cut-off value of IGs was 0.6%. The IGs > 0.6% had a sensitivity, specificity, and positive and negative predictive value of 100%, 96%, 85.7%, and 100%, respectively (area under the curve (AUC) = 0.98). On admission, SIRS was present in 25 (32%) patients. We found that in patients who fulfilled at least two criteria for SIRS, SAP could be predicted with 75% sensitivity and 75.4% specificity, positive predictive value 36%, negative predictive value 94.2%. Conclusions : The IGs% as a routinely obtained marker appears to be a promising, independent biomarker and a better predictor of early prognosis in SAP than SIRS and white blood cell.